MODEL TARIKAN PERJALANAN KE KAMPUS UNIVERSITAS MALIKUSSALEH BERDASARKAN KARAKTERISTIK PENGGUNA MODA TRANSPORTASI - Muhammad Isya; Lulusi Lulusi; Mukhlis Mukhlis (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2012)
Abstract: University of Malikussaleh located in the Reuleut Village within approximately 20 kilometers from the town of Lhokseumawe. For students, lecturer and university staff to go to this campus location can use some oftransportation mode, they are: public transport, private cars, and motorcycles. Selection of these modes depend on several factors. For that reason, it is necessary to study of the factors that influence the amount of trip attraction to the campus and create model based user characteristics. The objective this study is to determine the factors that influence the trip attraction to the campus of the University of Malikussaleh and create the transportation model of the trip for each mode. Data sample was collected by using a questionnaire to 349 respondents to construct linear regression model. Trip attraction models obtained are: public transport modes Y1 = -0.19 + 0.14 X1 + 0.54 X5; private car trip attraction models Y2 = 0.10 + 0.20 X1 + 0.01 X4; motorcycle trip attraction model is Y3 = 4.502 + 0.161 X1 + 0.011 X5, where X1 is the distance of residence, X4 is the age, and X5isthe family income.Keywords : Trip Attraction Model, Public Transport, Private Cars, MotorcyclesAbstrak: Universitas Malikussaleh berlokasi di Desa Reuleut berjarak lebih kurang 20 kilometer dari kota Lhokseumawe. Bagi mahasiswa, dosen dan pegawai untuk mencapai lokasi kampus inidapat menggunakan beberapa moda transportasi, yaitu:angkutan umum, mobil pribadi, dan sepeda motor. Untuk itu perlu dilakukan kajian tentang faktor-faktor yang mempengaruhi jumlah tarikan ke kampus ini berdasarkan karakteristik pengguna moda transportasi yang digunakan.Tujuan penelitian ini adalah untuk mengetahui faktor-faktor yang mempengaruhi tarikan perjalanan ke kampus Universitas Malikussaleh dan membuat suatu model tarikan perjalanan untuk setiap moda yang ditinjau. Pengambilan data dilakukan dengan penyebaran kuesioner terhadap 349 responden untuk membangun model regresi linier. Model tarikan perjalanan yang diperoleh adalah: moda angkutan umum Y1 = -0,19 + 0,14 X1 + 0,54 X5; model tarikan perjalanan mobil pribadi Y2 = 0,10 + 0,20X1 + 0,01 X4; model tarikan perjalanan sepeda motor yaitu Y3 = 4,502 + 0,161 X1 +0,011 X5, dimana X1adalah jarak tempat tinggal, X4 adalah umurdan X5pendapatan keluarga.Kata kunci : Model Tarikan Perjalanan, Angkutan Umum, Mobil Pribadi, Sepeda Motor.